Bioanalytical workflow for novel scaffold protein–drug conjugates: quantitation of total Centyrin protein, conjugated Centyrin and free payload for Centyrin–drug conjugate in plasma and tissue samples using liquid chromatography–tandem mass spectrometry. (25th October 2018) - Shi, Chuan; Goldberg, Shalom; Lin, Tricia; Dudkin, Vadim; Widdison, Wayne; Harris, Luke; Wilhelm, Sharon; Jmeian, Yazen; Davis, Darryl; O'Neil, Karyn; Weng, Naidong; Jian, Wenying
Aim: Alternative scaffold proteins have emerged as novel platforms for development of therapeutic applications. One such application is in protein–drug conjugates (PDCs), which are analogous to antibody–drug conjugates.Methodology: Liquid chromatography–mass spectrometry methods for quantitation of total protein, conjugate and free payload for a PDC based on Centyrin scaffold were developed. Tryptic peptides generated from a region of the Centyrin that does not contain a conjugation site, and another that has the conjugation site with the linker-payload attached were used as surrogates of the total and conjugated Centyrin, respectively.Conclusion: The methods were successfully applied to analysis of samples from mice to quantify the plasma and tissue concentrations. This same workflow can potentially be applied to other PDCs and site-specific antibody–drug conjugates.